Application of Clove Oil for Transportation and Anesthetic Maintenance of Juvenile Hybrid Catfish (Clarias macrocephalus x C.gariepinus) - Thanomsit, Chutima; Sonponkrung, Witsanu; Pimchan, Nittaya; Jantarakomet, Kraisak; Nanuam, Jakkaphun; Wattanakornsiri, Amnuay (Naresuan University Journal: Science and Technology (NUJST), 2021)
Synthetically chemical anesthetic might affect and accumulate in aquaculture fish when transportation of juvenile hybrid catfish. This study aimed: 1) to investigate the toxicity of clove oil, 2) to test the effectiveness of clove oil in application as an anesthetic in transportation, and 3) to evaluate appropriate concentrations of clove oil in using as an anesthetic. It was found that the cumulative mortality of hybrid catfish increased with an increasing in concentrations and exposure times. The mortality of hybrid catfish exposing to 10 ppm of clove oil was found after 48 h of exposure. For the concentrations of 20, 30 and 40 ppm of clove oil, the mortality was found after 24 h of exposure. The LC 50 of clove oil in hybrid catfish exposed to clove oil for 24, 48, 72 and 96 h were 66.26 (59.14-77.89), 50.54 (47.83 -54.14), 48.49 (44.63-53.79) and 35.67 (33.65-38.13) ppm, respectively. The concentrations of clove oil causing anesthetic (stage 3, e.g.loss of reflex activity) in the hybrid catfish were only 3 levels: 125, 150 and 175 ppm, respectively. EC 50 values were calculated in only 2 durations, which were found at 173.73 and 139.63 ppm, respectively. Finally, we found that the fish was recovered in 3 and 5 min. And, the EC 50 values were 111.96 (88.07-123.52) ppm and 165.09 (159.04-173.43) ppm. After evaluating the effectiveness of clove oil for fish transportation, all the concentrations comprising 2, 4, 6, 8 and 10 ppm did not cause fish mortality. The mucus in exposed fish was excreted more than in the normal condition after 15 h of exposure time and also found lesions on its body. Based on our results, clove oil could be used as an alternative agent in anesthetic maintenance and transportation in juvenile hybrid catfish. The appropriate concentrations of clove oil were in the range of 2-4 ppm.